Notes on Paratrichius Janson, 1881 inhabiting Hainan Island, with description of a new species and the definition of two new junior synonyms (Coleoptera: Scarabaeidae, Cetoniinae) - Ricchiardi, Enrico; Lu, Yuanyuan; Li, Sha; Ming, Bai (Fragmenta entomologica, 2022)
Nearly three decades ago two new species belonging to the genus Paratrichius Janson, 1881 were described from Hainan Island (SW China): Paratrichius papilionaceus Ma, 1990 and P. rufescens Ma, 1990. The present paper increases the number of Paratrichius species known from Hainan Island to four, with the description of a new species (P. pilosus Ricchiardi and Lu, n. sp.), and a new regional record for P. elegantulus (Moser, 1902), thus far known from N Indochina and continental SW China only. Additionally, Paratrichius papilionaceus Ma, 1990 is here proposed as junior synonym of Paratrichius marmoreus (Moser, 1902), described from northern Vietnam (n. syn.), and Paratrichius brevifolius Kobayashi and Fujioka, 2013, described from northern Vietnam, is here proposed as junior synonym of the above cited Paratrichius elegantulus (Moser, 1902) (n. syn.). Among the four Paratrichius species now listed from Hainan, two (P. pilous and P. rufescens) are very likely endemic to the island’s highlands, while other two inhabit the highlands of northern Vietnam, too.